Transformasi Epistemologi Pesantren dalam Menghadapi Tantangan Era Digital - M Nor Kholis; Muhammad Husni (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
Advances in digital technology have brought significant changes to Islamic education systems, including pesantren as one of Indonesia’s primary educational institutions. Digitalization influences learning patterns and creates epistemological impacts on traditional educational practices such as kitab kuning studies, sanad transmission, and the authority of the kiai. This study aims to analyze how pesantren scholars adapt their epistemological frameworks to remain relevant in the digital era while preserving classical values. Using a qualitative approach based on literature research, this study examines various aspects of digitalization challenges and the adaptive strategies implemented by pesantren. The findings indicate that the digital era presents several challenges, including shifting learning access, multitasking behavior, technological advancement, and the potential loss of traditional knowledge. However, digitalization also provides opportunities for santri to broaden their learning, access global literature, and enhance collaborative competencies. The transformation is carried out through digital literacy development, technology integration, increased teacher competence, and adaptive curriculum design. The ideal model is an integrative adaptive epistemology that employs technology as a tool to support, rather than replace, pesantren traditions.